Role of Parking Management in Urban Traffic Congestion: A Review (Indian Journal of Transport Engineering (IJTE), 2026)
Rapid urbanisation poses a serious transportation problem and is particularly pressing in developing nations. Inefficient parking management significantly affects traffic flow, roadway capacity, and the overall performance of transport systems. This review examines the relationship between parking characteristics and urban traffic congestion, drawing on recent academic articles, policy documents, and case-based findings. The main issues identified are over-parking on streets, insufficient organised parking supply, weak compliance with parking rules and policies, and poor integration of parking with land-use and public transportation planning. Taken together, these variables reduce the effective carriageway width, generate more traffic snarls, introduce regional bottlenecks and hold-ups, and worsen traffic congestion. The review focuses on current parking management strategies, including demand-responsive parking pricing, shared parking modes, smart parking technologies, regulatory enforcement, and connections to sustainable mobility planning. Special attention is focused on medium and small cities, characterized by insufficient infrastructure, mixed circulation, institutional bottlenecks and limitations in parking management. Results suggest that parking management forms an essential part of congestion mitigation strategies within urban transport planning.